2010
DOI: 10.1002/ar.21098
|View full text |Cite
|
Sign up to set email alerts
|

Ultramicroscopic Examination of the Ovine Tonsillar Epithelia

Abstract: As solid morphological knowledge of ovine tonsillar epithelia might contribute to a better understanding of the pathogenesis of several diseases including prion diseases, the epithelia of all tonsils of 7 one-yearold Texel sheep were examined using scanning and transmission electron microscopy. Major parts of the pharyngeal and tubal tonsils were covered by pseudostratified columnar ciliated epithelia that were interrupted by patches of epithelium containing cells with densely packed microfolds or microvilli, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 57 publications
11
38
0
Order By: Relevance
“…The signs of degeneration in the nuclei were more towards the free surface of the epithelium. Casteleyn et al, (2010) also made similar observations in the lingual tonsils of sheep. The presence of keratohyaline granules in the stratum superficiale was reported in the nonkeratinized epithelium of lingual tonsil in horse by Kumar and Timoney (2005b) and in goat by Kumar and Kumar (2005).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The signs of degeneration in the nuclei were more towards the free surface of the epithelium. Casteleyn et al, (2010) also made similar observations in the lingual tonsils of sheep. The presence of keratohyaline granules in the stratum superficiale was reported in the nonkeratinized epithelium of lingual tonsil in horse by Kumar and Timoney (2005b) and in goat by Kumar and Kumar (2005).…”
Section: Resultssupporting
confidence: 61%
“…5). Kumar and Kumar (2005) and Casteleyn et al, (2010) made similar observations on the morphology of the tonsils in goats and sheep, respectively. Large numbers of lymphocytes were seen in the propria submucosa (Fig.…”
Section: Resultsmentioning
confidence: 67%
“…Studies of the ovine pharyngeal tonsil identified a heterogeneous population of microvillus containing cells (i.e. M-cells) (Chen et al, 1991;Casteleyn et al, 2010). Such cells have been variably described as electron dense or electron lucent, flattened, cuboidal or columnar, and covered with microfolds, microvilli, or both microvilli and cilia.…”
Section: Discussionmentioning
confidence: 99%
“…Terminology of Mv1, Mv2, In, S etc. was adapted from previous examination of the ovine pharyngeal tonsil (Casteleyn et al, 2010) and equine pharyngeal tonsil (Kumar and Timoney, 2001; Table 2). …”
Section: Semmentioning
confidence: 99%
See 1 more Smart Citation